Hubungan Sosialisasi dan Sumber Informasi Dengan Pengetahuan Mahasiswa Tentang Pelecehan Seksual - Nompo, Rifki Sakinah; Asmuruf, Kristina (Yayasan Healing and Healthcare Education, 2025)
Sexual harassment is a serious issue that occurs in various settings, including higher education institutions. Students’ knowledge of sexual harassment is essential for prevention efforts. This study aims to determine the relationship between socialization and sources of information with students’ knowledge of sexual harassment. Methode use a quantitative correlational design was employed with a total of 173 students selected using accidental sampling. The research instruments included questionnaires on socialization, sources of information, and knowledge of sexual harassment. Data were analyzed using the Chi-Square test. Statistical analysis revealed no significant relationship between socialization and knowledge of sexual harassment (p = 0.565). However, a significant relationship was found between sources of information and knowledge of sexual harassment (p = 0.000). Socialization activities have not yet been effective in enhancing student knowledge regarding sexual harassment. Conversely, access to diverse sources of information significantly contributes to improving students’ understanding of the issue.